2017
DOI: 10.1089/fpd.2016.2241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-Lethal Concentrations of Biocides on the Structural Parameters and Viability of the Biofilms Formed by Salmonella Typhimurium

Abstract: This study aimed to investigate the effect of sub-minimum inhibitory concentrations (sub-MICs) of three food-grade biocides (benzalkonium chloride -BZK-, trisodium phosphate -TSP-, and sodium hypochlorite -SHY-) on Salmonella biofilms. The structural parameters and bacterial viability of the biofilms formed by a S. Typhimurium isolate from poultry was investigated by means of confocal laser scanning microscopy after staining with SYTO9 and propidium iodide. The MIC values for Salmonella cells before exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 12 publications
8
21
0
Order By: Relevance
“…Structural parameter values in the present work are also similar to those previously observed for biofilms formed on polystyrene by a S . Typhimurium isolate from food (S175), as recorded by Capita et al [ 2 ]. It should be noted that in both the above-mentioned papers only fluorescent dyes for staining nucleic acids were used, and the EPS matrix was not studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural parameter values in the present work are also similar to those previously observed for biofilms formed on polystyrene by a S . Typhimurium isolate from food (S175), as recorded by Capita et al [ 2 ]. It should be noted that in both the above-mentioned papers only fluorescent dyes for staining nucleic acids were used, and the EPS matrix was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella has the ability to form biofilms, which have been identified as an important factor for the persistence of food-borne pathogens in food-processing environments [ 2 , 3 , 4 ]. Salmonella Agona strains have been classified as strong biofilm producers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of biofilms is a survival strategy adopted by bacterial cells in response to the damage caused by environmental stressors, such as sub-lethal concentrations of antimicrobial and oxidizing agents [ 146 , 147 , 148 ]. The molecular mechanisms involved in biofilm stimulation by these stressors have not been elucidated.…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…It was observed that contact between biofilms and BZK increased the amount of biomass (markedly so for concentrations of 2500 ppm). An enhanced ability to form a biofilm in the presence of BZK has previously been demonstrated for strains of Escherichia coli [72], methicillin-resistant Staphylococcus aureus (MRSA) [73], Salmonella [71,74], and L. monocytogenes [14]. In the present study, the biofilms were exposed to BZK for five minutes and the biocide was then eliminated, although it is probable that residual quantities remained in the wells of the microtiter plate.…”
Section: The Effect Of Disinfectants On Biofilmsmentioning
confidence: 70%